2020
DOI: 10.1029/2019jf005419
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Transit Time and Floodplain Storage Dynamics in Alluvial Rivers Revealed by Meteoric10Be

Abstract: Quantifying the time scales of sediment transport and storage through river systems is fundamental for understanding weathering processes, biogeochemical cycling, and improving watershed management, but measuring sediment transit time is challenging. Here we provide the first systematic test of measuring cosmogenic meteoric Beryllium-10 (10 Be m) in the sediment load of a large alluvial river to quantify sediment transit times. We take advantage of a natural experiment in the Rio Bermejo, a lowland alluvial ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 66 publications
2
61
1
Order By: Relevance
“…These temporal and anthropic fluctuations will contribute to the geochemical variability not explained by our model. We note that cosmogenic nuclide studies suggest that the average residence time of sediment in drainage basins is likely to be of the order of hundreds to thousands of years (Repasch et al., 2020). These observations suggest that the composition of sediment in drainage basins might integrate processes operating on timescales of hundreds to thousands of years.…”
Section: Discussionmentioning
confidence: 88%
“…These temporal and anthropic fluctuations will contribute to the geochemical variability not explained by our model. We note that cosmogenic nuclide studies suggest that the average residence time of sediment in drainage basins is likely to be of the order of hundreds to thousands of years (Repasch et al., 2020). These observations suggest that the composition of sediment in drainage basins might integrate processes operating on timescales of hundreds to thousands of years.…”
Section: Discussionmentioning
confidence: 88%
“…The duration of sediment storage outside the active river channel can also be measured from the ratio of cosmogenic meteoritic 10 Be over 9 Be within sediments (Wittmann et al, 2015). Repasch et al (2020) tested this method along the Rio Bermejo (Andean foreland basin, northern Argentina) and observed that the suspended load travels ∼1200 km from sources to sink in 8.4 ± 2.2 kyr.…”
Section: Quantification Of Sediment Transport Timesmentioning
confidence: 99%
“…The duration of sediment storage outside the active channel can also be measured from the ratio of cosmogenic meteoritic 10 Be over 9 Be within sediments (Wittmann et al, 2015). Repasch et al (2020) tested this method along the Rio Bermejo (Andean foreland basin, northern Argentina) and observed that the suspended load travels ~1200 km from sources to sink in 8.4±2.2 kyr. Within the Indus SRS, Clift et al (2008) suggests based on Nd composition on a limited set of samples, that the clay-sized fraction travels as suspended load rapidly through the system after an increase in monsoon strength with no resolvable lag time, while the bedload transport is decoupled from the suspended load and heavy mineral (zircon) grains travel about of 7-14 kyr from source to sink (Clift and Giosan, 2014).…”
Section: Quantification Of Sediment Transport Timesmentioning
confidence: 99%